2016
DOI: 10.1016/j.joep.2015.07.001
|View full text |Cite
|
Sign up to set email alerts
|

The significance of financial self-efficacy in explaining women’s personal finance behaviour

Abstract: Much policy attention has been placed on enhancing individuals' financial knowledge and literacy, chiefly through financial education programs. However, managing one's personal finances takes more than financial knowledge and literacy: an individual also needs a sense of self-assuredness, or 'self-belief', in their own capabilities. This personal attribute is known within the psychology literature as 'self-efficacy'. This paper examines the significance of an individual's financial self-efficacy in explaining … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

27
272
2
9

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 300 publications
(310 citation statements)
references
References 36 publications
27
272
2
9
Order By: Relevance
“…In other words, those participants who believed they possessed a high degree of confidence in their ability to handle their finances anticipated less difficulty in paying off their loans as compared to those participants who reported less confidence in their ability. This finding supports previous evidence linking financial self‐efficacy to other positive financial outcomes, such as the level of financial knowledge achieved (Lown et al ), the value of financial assets owned (Farrell, Fry, and Risse ), whether a retirement plan had been formalized (Dietz, Carrozza, and Ritchey ), and whether proactive financial planning had occurred (Lim et al ).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…In other words, those participants who believed they possessed a high degree of confidence in their ability to handle their finances anticipated less difficulty in paying off their loans as compared to those participants who reported less confidence in their ability. This finding supports previous evidence linking financial self‐efficacy to other positive financial outcomes, such as the level of financial knowledge achieved (Lown et al ), the value of financial assets owned (Farrell, Fry, and Risse ), whether a retirement plan had been formalized (Dietz, Carrozza, and Ritchey ), and whether proactive financial planning had occurred (Lim et al ).…”
Section: Discussionsupporting
confidence: 89%
“…Among college students, financial self‐efficacy has been shown to be positively associated with well‐being and academic persistence (Robb ; Robb and Woodyard ). Related studies found that individuals with a stronger sense of financial self‐efficacy were more likely to own such financial assets as investment and savings products (Farrell, Fry, and Risse ), and to have formulated retirement plans (Dietz, Carrozza, and Ritchey ), and to engage in consultation with financial planning services (Lim et al ; Neymotin ).…”
Section: Conceptual Model Development and Hypothesesmentioning
confidence: 99%
“…In reading and writing literacy, self‐efficacy involves a willingness to try that supports gains in literacy (Schunk ). In the realm of household finance, self‐efficacy is associated with positive financial behaviors and outcomes (Asebedo and Seay ; Chatterjee, Finke, and Harness ; Farrell, Fry, and Risse ). Higher levels of self‐efficacy correlate with financial well‐being (CFPB ), the setting of more challenging goals (Bandura ), and the facilitation of financial help‐seeking (Lim et al ).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Risky credit card behaviors were associated with lower well‐being levels in college students (Gutter & Copur, ). Farrell et al () provided evidence that suggests those with higher FSE are less likely to hold debt‐related products entirely. Similarly, those with a lower RT were less likely to be convenience credit card users (Rutherford & DeVaney, ).…”
Section: Literature Review and Hypothesesmentioning
confidence: 99%
“…This subjective component of FSE facilitates the sense of resiliency and ability to adjust and respond to financial events and circumstances. Given the theoretical relationship between selfefficacy and the self-regulatory process (Bandura, 1991), it is not surprising that researchers have found FSE to predict several positive financial behaviors (e.g., see Farrell, Fry, & Risse, 2016;Lown, 2011;Shim, Serido, & Tang, 2012).…”
Section: Introductionmentioning
confidence: 99%